Efficiency of small mammal trapping in an Atlantic Forest fragmented landscape: the effects of trap type and position, seasonality and habitat - ALM Vieira; AS Pires; AF Nunes-Freitas; NM Oliveira; AS Resende; EFC Campello (Brazilian Journal of Biology)
Trapping methods can strongly influence the sampling of mammal communities. This study compared the efficiency of the capture of small mammals in Sherman traps in two positions (at ground level and in trees) and pitfall traps in a fragmented landscape. Trapping sessions were carried out between October 2008 and October 2009 at two fragments (8 and 17 ha), an agroforest corridor between them, and the adjacent pasture. A total effort of 4622 trap-nights resulted in 155 captures of 137 individuals from six species. Pitfalls had greater success (4.03%), followed by Shermans on the ground (2.98%) and on trees (2.37%; χ2= 6.50, p = 0.04). Five species were caught in Sherman ground traps, four in pitfalls and just two on trees. There was no difference among trap types for marsupials (χ2 = 4.75; p = 0.09), while for rodents, pitfalls were more efficient than Shermans on the ground (Fisher's exact test, p = 0.02). As a result, the efficiency of each trap type differed among habitats, due to differences in their species composition. Pitfalls were more efficient in the rainy season (Fisher's exact test, p <0.0001) while Shermans on trees were more efficient in the dry season (Fisher's exact test, p = 0.009). There was no difference between seasons for Shermans on the ground (Fisher's exact test, p = 0.76). Considering the results found, we recommend that future studies of forest mammal communities, particularly those designed to test the effects of forest fragmentation, include combinations of different trap types.